Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd003842.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Single, double or multiple-injection techniques for non-ultrasound guided axillary brachial plexus block in adults undergoing surgery of the lower arm

Abstract: This review provides evidence that multiple-injection techniques using nerve stimulation for axillary plexus block produce more effective anaesthesia than either double or single-injection techniques. However, there was insufficient evidence for a significant difference in other outcomes, including safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…The 92% rate of successful blockade in our metaanalysis is higher than previously described, despite injecting 20-35 ml of local anaesthetic compared with 40-50 ml used in trials of axillary brachial plexus blocks without ultrasound [3] and infraclavicular brachial plexus block with or without ultrasound [46], which reported success rates of 76% and 88%, respectively. It is likely that ultrasound guidance allows a more accurate and efficient deposition of perineural local anaesthetic [5,47,48].…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The 92% rate of successful blockade in our metaanalysis is higher than previously described, despite injecting 20-35 ml of local anaesthetic compared with 40-50 ml used in trials of axillary brachial plexus blocks without ultrasound [3] and infraclavicular brachial plexus block with or without ultrasound [46], which reported success rates of 76% and 88%, respectively. It is likely that ultrasound guidance allows a more accurate and efficient deposition of perineural local anaesthetic [5,47,48].…”
Section: Discussioncontrasting
confidence: 69%
“…A single injection was as effective as multiple injections and took less time and caused less paraesthesia. Multiple injections were more effective than a single injection in a recent systematic of axillary brachial plexus blocks performed without ultrasound [3], which suggested that plexus location using anatomical landmarks, paraesthesia or nerve stimulation was inaccurate. It has been suggested that septae might prevent the flow of local anaesthetic around all nerves in a plexus [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chin et al . also conducted a Cochrane systematic review on axillary plexus block, assessing single, double, and multiple injection techniques 23 . In all, 21 trials were included, presenting results from a total of 2148 participants who received regional anaesthesia for hand, wrist, forearm, or elbow surgery.…”
Section: Efficacy and Outcomementioning
confidence: 99%
“…This supports the established recommendation to use multiple injections when performing axillary blocks. 11 …”
Section: Discussionmentioning
confidence: 99%